MANAGEMENT OF THE CLIMACTERIC WITH DIGITAL TOOLS: SUPPORT FOR HORMONE THERAPY AND SYMPTOM CONTROL - Borges, Paulo Roberto Pereira; da Silva, Edna Maria; Cordeiro, Priscila Vanderli; da Silva, Lilian Bibiane; Zaparoli, Sarah Fernandes; da Rocha, Patrícia; Prado, Kailane Silva; da Costa, Maria Eduarda Vicente Alves; Andrade, Bianca Costa; Santos, Iarla Kayane Araújo (Seven Editora, 2026)
The climacteric is a transitional phase in the female reproductive cycle characterized by progressive hormonal changes, especially the reduction of estrogen levels, which may trigger physical, emotional, and psychosocial manifestations with a significant impact on women’s quality of life. In this context, the adequate management of climacteric symptoms represents a challenge for health services, particularly within Primary Health Care, requiring comprehensive, continuous, and woman-centered care strategies. Hormone therapy stands out as one of the main interventions for symptom relief, provided it is used in an individualized manner and based on scientific evidence. However, factors such as misinformation, fear of adverse effects, and difficulties in regular follow-up may compromise therapeutic adherence. Therefore, digital health tools emerge as strategic resources to support hormone therapy and symptom control during the climacteric. This study aimed to analyze the use of digital tools in climacteric management, with an emphasis on supporting hormone therapy and promoting self-care. This is an integrative literature review based on the analysis of scientific articles and national and international regulatory documents related to women’s health, digital health technologies, and public health policies. The results showed that mobile applications, digital platforms, and telehealth strategies contribute to continuous symptom monitoring, strengthen communication between users and health professionals, and favor adherence to hormone therapy. It is concluded that the incorporation of digital tools, when integrated into healthcare practices and in compliance with ethical and legal principles, has the potential to improve the quality of care for women during the climacteric, promoting autonomy, comprehensive care, and quality of life.DOI: https://doi.org/10.56238/sevened2026.002-002